A Proposal to Create a Human Rights Observatory at the Law Faculty of the Universidad Cooperativa de Colombia, Bucaramanga Campus - Rueda Puyana, Ernesto; Morantes Avendaño, Hernan Alberto; Calderón Calderón, Yeni Yuliet (DIXI, 2015)
Ths article aims to analyze the crisis in human rights, framed within the national and regional contexts, as a source of concern for academia. Because of its role in society, academia has the duty and obligation to contribute towards scientifi knowledge based on its research work in response to social needs while helping to solve problems in the country. In this sense and in the framework of this research, an organic and theoretical structure is proposed for a human rights observatory at the Law Faculty of the Bucaramanga campus of the Universidad Cooperativa de Colombia. Ths would be an indispensable research instrument, not only to help train students in the ability for critical, reflxive and free thought, but also to contribute necessary scientifi knowledge to ascertain the social reality and provide solutions for the problems in Colombia in the fild of human rights. A qualitative conception has served as the basis for the interpretive method. Concerned about occurrences in the country and focusing on research into events in their natural context, we have based this work on a qualitative conception in carrying out the research.